GLOBALLY STANDARDIZED ASSESSMENT OF RELIGIOUS MODERATION LITERACY IN PRIMARY EDUCATION: VALIDITY AND RELIABILITY EVIDENCE - Tri Sutrisno; Neni Mariana; Nadi Suprapto; Suryanti Suryanti; Samar Solehan (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
Abstract: This study aimed to develop a valid and reliable assessment instrument for measuring religious moderation literacy in elementary schools. The research adopted Plomp’s development model, comprising three phases: preliminary research, prototyping, and assessment. The validity of the instrument was examined using two approaches: expert validation, assessing content, construct, and language, and empirical testing with 20 students at Cangkreng 1 Public Elementary School, Sumenep Regency, Indonesia. The results indicated that the developed assessment instrument, consisting of 12 essay items, was both valid and reliable. Content validity achieved a mean score of 3.65 (very high) with Cronbach’s alpha (α) = 0.88; construct validity averaged 3.56 (highly valid) with α = 0.87; and language aspects averaged 3.78 with α = 0.90, with an inter-rater agreement of 87%. In the limited field testing, all 12 items (Items 01–12) demonstrated Pearson correlations ranging from 0.738 to 0.954 with total scores (p < 0.001), indicating statistical significance. As all correlation coefficients exceeded the critical value (r table = 0.444; df = 18; α = 0.05), every item was considered valid for measuring religious moderation literacy among elementary school students. The overall reliability of the instrument reached α = 0.982 (very high). The developed instrument can serve as a valid and reliable tool for assessing religious moderation literacy in primary education. However, further evaluation of its effectiveness and development using alternative models is recommended